Intellectual achievement in pursuit of true belief - Shapiro, Lucy Deborah (Rhodes University, Faculty of Humanities, Department of Philosophy, 2006)
The practice of inquiry, in which we seek and pursue true beliefs by forming justified beliefs, is important to us. This thesis will address two questions concerning the significance of this practice. These are the question of what explains our preference for this particular belief-forming practice, and whether this value can be explained by the value of true belief alone. To answer these questions I will examme a variety of our intuitive commitments to particular values, assuming their general accuracy. I will use an inference from the goal of a practice to the value of a practice, an inference based on the assumption that when we pursue something it is valuable. I will discuss our intuitive commitments to the value of justification. I will also rely on the implications of the presence of pride and admiration in relation to the outcome of an inquiry (especially in situations where a belief is difficult to form). By using this methodology, I will argue for three sources of value that explain the unique significance of the value of inquiry. The first is the value of its unique role in our being able to form reliably true beliefs. Second, I will argue for Wayne D. Riggs' account of epistemic credit; Riggs defends the value of our being responsible for true beliefs, they are our achievements. Third, I will argue for an additional the value of delivering a skilful epistemic performance, another kind of achievement. I will show that although the value of true belief plays a role in explaining some of the values, the third value for inquiry is independent of the value of true belief. This means that there are intellectual rewards, which can be gained from this practice, that extend beyond the value of true belief.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Delusions; Knowledge, Theory of; Epistemics; Truth